The potential role of Egypt as a natural gas supplier: A review. (November 2022) - Esily, Rehab R.; Chi, Yuanying; Ibrahiem, Dalia M.; Amer, Mustafa A.
Abstract: The energy sector is the most greenhouse gas (GHG) emitting sector which is transitioning away to using less carbon-intensive fuels. The highlights the complexity of energy systems as well as the uncertainty surrounding the transition path, as governments must ensure not only environmental issues but also energy security and affordability. The energy transition away from oil and gas has implications for Egypt, which recently declared intentions to become a liquefied natural gas (LNG) export hub. Under these goals, the analysis of the existing status of global natural gas markets by focusing on natural gas importer countries in the European and the Asian markets by investigating natural gas demand in the context of the energy transition. The study investigates the links between economic growth, carbon emissions, and energy intensity to highlight the dependency of the economy on carbon-intensive energies to enhance the economic growth in Egypt, Europe, and Asia along with global energy pathways forecast the global and regional demand of natural gas. According to the findings, Egypt is expected to face difficulties in boosting its export share in the European market while the most promising destinations for future Egyptian natural gas exports are Asian countries. The study contextualizes the framework, which suggests the ways to reduce emissions in the gas upstream sector in Egypt by three actions; reducing flaring and venting operations, improving well integrity management, and regulating the abandonment of old wells. Highlights: Egypt natural gas exporting hub ambition. Delink between GDP and CO2 emissions. Egypt in a decarbonized Europe. Egypt is a competitive supplier of LNG in Asian markets.